Effect of space allowance and floor type on performance, welfare and physiological measurements of finishing beef heifers. (21st June 2017) - Keane, M. P.; McGee, M.; O'Riordan, E. G.; Kelly, A. K.; Earley, B.
Abstract : Accommodating cattle indoors during the winter is widely practiced throughout Europe. There is currently no legislation surrounding the space allowance and floor type that should be provided to cattle during this time, however, concerns have been raised regarding the type of housing systems currently in use. The objective of the study was to investigate the effect of space allowance and floor type on performance and welfare of finishing beef heifers. Continental crossbred heifers ( n =240: mean initial live; weight, 504 (SD 35.8) kg) were blocked by breed, weight and age and randomly assigned to one of four treatments; (i) 3.0 m 2, (ii) 4.5 m 2 and (iii) 6.0 m 2 space allowance per animal on a fully slatted concrete floor and (iv) 6.0 m 2 space allowance per animal on a straw-bedded floor, for 105 days. Heifers were offered a total mixed ration ad libitum. Dry matter intake was recorded on a pen basis and refusals were weighed back twice weekly. Heifers were weighed, dirt scored and blood sampled every 3 weeks. Whole blood was analysed for complete cell counts and serum samples were assayed for metabolite concentrations. Behaviour was recorded continuously using IR cameras from days 70 to 87. Heifers' hooves were inspected for lesions at the start of the study and again after slaughter. Post-slaughter, carcass weight, conformation and fat scores and hide weight were recorded. Heifers housed at 4.5 m 2 had a greater average daily live weight gain (ADG) than those on both of the other concrete slat treatments; however, space allowance had no effect on carcass weight. Heifers accommodated on straw had a greater ADG (0.15 kg) ( P <0.05), hide weight ( P <0.01) better feed conversion ratio ( P <0.05) and had greater dirt scores ( P <0.05) at slaughter than heifers accommodated on concrete slats at 6.0 m 2 . The number of heifers lying at any one time was greater ( P <0.001) on straw than on concrete slats. Space allowance and floor type had no effect on the number of hoof lesions gained or on any of the haematological or metabolic variables measured. It was concluded that increasing space allowance above 3.0 m 2 /animal on concrete slats was of no benefit to animal performance but it did improve animal cleanliness. Housing heifers on straw instead of concrete slats improved ADG and increased lying time; however carcass weight was not affected.